BENTHIC FORAMINIFERA RESPONSE TO METHANE RELEASE INAN ADRIATIC SEA POCKMARK (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
The presence of methane-bearing shallow sediments in the Adriatic Sea has been known since the fifties, but little is known about the benthic foraminiferal assemblages associated with them. One seep and two control cores were collected in the Bonaccia field (central Adriatic Sea) at a water depth of 80 m to investigate the possible influence of the release of gas from marine reservoirs on these foraminiferal assemblages. The seep core was drilled inside a pockmark in the vicinity of an active mud-volcano. Two control cores were collected in nearby areas unaffected by presence of methane. Benthic foraminiferal assemblages from the seep core are comparable to those from the seep-free cores and are composed of species common in the central Adriatic Sea. However, foraminiferal density in the seep-core is remarkably lower than in the control ones cores. Besides, calcitic foraminiferal tests from the seep core revealed unusual trends in stable carbon isotope composition. Even though not within the same range, a similar trend was observed throughout the seep core for the ä13C values of Gavelinopsis lobatulus, Cassidulina carinata, and Bulimina marinata. In particular, negative carbon isotope values were recorded for Gavelinopsis lobatulus at the top of the core where methane seeps were detected and deep inside the core sediments (50 cm). These findings seem to point to temporal variations in seep activity, proving that the ä13C values of foraminiferal tests reflect hydrocarbon release and may hence be used to reconstruct seep activity history.• Table 1 (all.): Number of benthic foraminifera from GAB1core samples• Table 2 (all.): Foraminiferal percent of the total benthic foraminiferal fauna from GAB1 core samples• Table 3 (all.): Number of benthic foraminifera from GAB2 core samples.• Table 4 (all.): Foraminiferal percent of the total benthic foraminiferal fauna from GAB2 core samples.• Table 5 (all.): Number of benthic foraminifera from GAB3 core samples.• Table 6 (all.): Foraminiferal percent of the total benthic foraminiferal fauna from GAB3 core samples.